Performance of ZnO Nanoparticles for Fire Retardant and UV Protection of Pine Wood - Favarim, Higor Rogerio [UNESP]; Leite, Lucas Oliveira [UNESP] (North Carolina State Univ Dept Wood & Paper Sci, 2018)
The aim of this paper was to investigate the influence of zinc oxide (ZnO) nanoparticles on the resistance of pine wood to fire and ultraviolet (UV) radiation. The ZnO nanoparticles were prepared from aqueous zinc nitrate via a proteic sol-gel method. Dried samples were impregnated using immersion in an aqueous solution of ZnO nanoparticles in the amount of 1 wt.% wood. Samples were exposed to an open flame to test the fire retardance, and a high-pressure UV lamp was used to test the UV resistance. The results showed an improvement in the fire retardance and UV radiation resistance after the impregnation of ZnO nanoparticles.
Keywords: ZnO nanoparticles; Pine wood; UV resistance; Fire resistance; Proteic sol-gel method